1992
DOI: 10.1523/jneurosci.12-05-01847.1992
|View full text |Cite
|
Sign up to set email alerts
|

Synapses formed by identified retinogeniculate axons during the segregation of eye input

Abstract: The synaptic organization of identified retinogeniculate axons was studied during the prenatal development of eye-specific layers in the LGN of the cat. During this period, retinogeniculate axons undergo stereotyped morphological changes. Retinogeniculate axons originating from one eye and passing through LGN territory destined to be solely innervated by the other eye (inappropriate territory) initially give rise to many side branches. As the eye-specific layers emerge, these axons elaborate extensive terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 47 publications
2
66
0
Order By: Relevance
“…Visualization of synaptic vesicle distribution along axon arbors in fixed tissues showed punctate synaptic protein localization along the entire extent of the arbor (20,21), suggesting that synapses are evenly distributed along the axon arbor. Electron microscopy studies also revealed that ul-trastructurally identified synapses are localized throughout the axon arbor (22,23), an observation recently confirmed by in vivo imaging studies (8). In more mature arbors, however, ultrastructurally identified synapses are preferentially localized to distal end branches (23).…”
Section: Synaptogenesis: a Microscopic Viewmentioning
confidence: 64%
“…Visualization of synaptic vesicle distribution along axon arbors in fixed tissues showed punctate synaptic protein localization along the entire extent of the arbor (20,21), suggesting that synapses are evenly distributed along the axon arbor. Electron microscopy studies also revealed that ul-trastructurally identified synapses are localized throughout the axon arbor (22,23), an observation recently confirmed by in vivo imaging studies (8). In more mature arbors, however, ultrastructurally identified synapses are preferentially localized to distal end branches (23).…”
Section: Synaptogenesis: a Microscopic Viewmentioning
confidence: 64%
“…Another important factor may be the depolarized levels of the resting membrane potential at early postnatal ages, which may contribute to an increased duration of excitatory postsynaptic potentials at the immature retinogeniculate synapse (Ramoa and McCormick, 1994). Enhanced excitatory transmission may be especially important at a time when synapses probably release fewer quanta of neurotransmitter per action potential than in the adult (Campbell and Shatz, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In mice and ferrets, eyespecific retinogeniculate segregation occurs during the first ten days of postnatal life (P1-10) (Godement et al 1984,Jaubert-Miazza et al 2005 (Figure 1). Individual-axon labeling studies indicate that eyespecific segregation reflects two general processes: (a) synapse and axon arbor elaboration and (b) synapse and axon arbor elimination (Campbell & Shatz 1992;Sretavan & Shatz 1984, 1987. Electrophysiological recordings indicate that before segregation, RGC axons from both eyes can drive activity in individual LGN neurons.…”
Section: Eye-specific Segregation In the Lgnmentioning
confidence: 99%